El discurso antifeminista como recurso electoral en Brasil y España - Castillo Jara, Soledad (2019)
This paper focuses on two cases corresponding to parties and candidates situated more to the right than usual and, therefore, described as far right. These cases are Jair Bolsonaro, former candidate of the Social Liberal Party and current president of Brazil after winning in the second round of the general elections of October 7, 2018 with 55.1% of the votes; and Vox, the party which achieved parliamentary representation in Spain for the first time after the general elections of April 28, 2019 and is currently the third parliamentary force with 15, 09 % of the votes and 52 seats.For both, we propose to study the use of anti-feminist political discourse as an electoral tool. In spite of the differences in the electoral systems and in the institutional designs of both countries - one presidential and the other parliamentary - both cases share the fact that the candidates have managed to convince the electors, although in different degrees, appealing to discontent against the progressive ideas and policies of the previous leftist governments, that of the Workers Party (PT) in Brazil and that of the Socialist Party (PSOE) in Spain. Evidently, among these ideas is the struggle for gender equality that is described by the extreme right parties as a "gender ideology." We conclude that, although both use a discourse which is at odds with feminism, the questioning they present does not attack the whole set of ideas of that movement. Instead, it is directed against the most contemporary or post-material ones (such as the quota system or inclusive language), while recognizing and even praising the most classic or material achievements of feminism (such as women's economic independence). Additionally, there is a greater complexity in the debate in Spain, which leads us to think that the questioning raised by Vox may be useful to rethink the progressive ideas and policies of the last governments in a more general way, which transcends the scope of gender.